2009
DOI: 10.1007/s10775-009-9163-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy beliefs and the relation between career planning and perception of barriers

Abstract: This study tested the hypothesis that self-efficacy in career roles moderates the relation between perception of career barriers and career planning, in a study with Portuguese students, 488 in Grade 9 and 517 in Grade 12. The results supported the hypothesis only among Grade 9 girls, showing that perception of career barriers leads to less career planning among girls low in self-efficacy. The findings suggest that variables such as gender and psychological maturity need to be considered in understanding caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…Despite the general similarity between male and female students in the remaining competencies, it is curious to notice that female students have lower perceptions of preparedness for labor market transition and lower expectations of success in that transition. These results are consistent with previous studies indicating that women score higher than men in measures of perception of career barriers (Cardoso & Ferreira Marques, 2001;Cardoso & Moreira, 2009;McWhirter, 1997), with subsequent impact in career planning (Cardoso & Moreira, 2009). Indeed, several studies have confirmed differences in various career outcomes across different fields, such as earning, promotions and occupation of executives' positions (Bertrand, Goldin, & Katz, 2010;Gayle, Golan, & Miller, 2012;Ginther & Hayes, 1999;Ginther & Kahn, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the general similarity between male and female students in the remaining competencies, it is curious to notice that female students have lower perceptions of preparedness for labor market transition and lower expectations of success in that transition. These results are consistent with previous studies indicating that women score higher than men in measures of perception of career barriers (Cardoso & Ferreira Marques, 2001;Cardoso & Moreira, 2009;McWhirter, 1997), with subsequent impact in career planning (Cardoso & Moreira, 2009). Indeed, several studies have confirmed differences in various career outcomes across different fields, such as earning, promotions and occupation of executives' positions (Bertrand, Goldin, & Katz, 2010;Gayle, Golan, & Miller, 2012;Ginther & Hayes, 1999;Ginther & Kahn, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Second, we expected that perceived career barriers would inhibit career engagement (e.g., Cardoso & Moreira, ). Our results did not support this assumption at the within‐individual level, showing that the longitudinal approach chosen in the present study adds important insight into this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the practical relevance of career barriers, qualitative studies have shown that college students report perceiving different barriers that are personal, social, or labor‐market specific (Lent et al, ; Swanson & Tokar, ). Quantitative research (Lucas & Epperson, ) has confirmed that perceived barriers are related to career indecision, lower career expectations (Creed, Conlon, & Zimmer‐Gembeck, ), and less career planning among girls low in self‐efficacy (Cardoso & Moreira, ).…”
Section: Motivational and Social‐cognitive Predictors Of Career Engagmentioning
confidence: 99%
“…Because career resilience involves the development of coping strategies to overcome career obstacles (Bimrose & Hearne, 2012;Cardoso & Moreira, 2009), it is an important avenue of potential intervention by career counselors and HR practitioners. The creation of such interventions requires a better understanding of the antecedents and consequences of career resilience.…”
Section: Theoretical Modelmentioning
confidence: 99%